2021
DOI: 10.3897/mycokeys.77.60077
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the genus Sugiyamaella and description of two new species from rotting wood in China

Abstract: Species of the genus Sugiyamaella (Trichomonascaceae, Saccharomycetales), found in rotting wood in China, were investigated using morphology and the molecular phylogeny of a combined ITS and nrLSU dataset. Nine taxa were collected in China: two were new species (viz. Sugiyamaella chuxiongsp. nov. and S. yunanensissp. nov.) and seven were known species, S. americana, S. ayubii, S. novakii, S. paludigena, S. valenteae, S. valdiviana and S. xiaguanensis. The two new species are illustrated and their morphology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…Several yeast species (e.g., species of Spathaspora , Scheffersomyces , and Sugiyamaella clades) found in the guts and frass of wood‐boring insects were also found in their habitats, including rotting wood (Lopes et al, 2018a; Nguyen et al, 2006; Shi et al, 2021). Yeasts found in decomposing wood have been shown to often have the ability to assimilate and/or ferment lignocellulosic sugars, especially pentoses from the hemicellulosic fraction (Barros et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several yeast species (e.g., species of Spathaspora , Scheffersomyces , and Sugiyamaella clades) found in the guts and frass of wood‐boring insects were also found in their habitats, including rotting wood (Lopes et al, 2018a; Nguyen et al, 2006; Shi et al, 2021). Yeasts found in decomposing wood have been shown to often have the ability to assimilate and/or ferment lignocellulosic sugars, especially pentoses from the hemicellulosic fraction (Barros et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The internal transcribed spacer (ITS) regions and the D1/D2 domains of the large subunit (LSU) rRNA gene were amplified using the primer pairs ITS1/ITS4 ( White et al, 1990 ) and NL1/NL4 ( Kurtzman and Robnett, 1998 ), respectively. The PCR program was as follows: initial denaturation at 95°C for 3 min; 35 cycles of 94°C for 40 s, 56°C for 45 s, and 72°C for 1 min; and a final extension of 72°C for 10 min ( Shi et al, 2021 ). PCR products were cleaned and sequenced by Sangon Biotech Inc.…”
Section: Methodsmentioning
confidence: 99%
“…The Sugiyamaella genus has a worldwide distribution, and most of its species were originally found in Europe, North and South America and, more recently, in China. They were isolated either directly from wood-ingesting insects and insect frass, or from common insect habitats, such as rotting wood, forest soil, mushrooms, and peat [ 29 ]. In conclusion, it was shown that the analysis of samples with a prevailing (>60%) and atypical genus RA could help to infer the presumable impact of long-range transported air masses on the Ascomycota and Basidiomycota genera community structures, as found for the Streptophyta genera.…”
Section: Resultsmentioning
confidence: 99%